EPIDEMIOLOGY OF TYPE 2 DIABETES MELLITUS IN ADULTS AGED 40 YEARS AND OLDER: PREVALENCE, DEMOGRAPHIC CHARACTERISTICS, AND REGIONAL DIFFERENCES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Type 2 diabetes mellitus (T2DM) has emerged over the past decades as one of the most pressing non-communicable diseases confronting global health systems. Population aging, rapid urbanization, lifestyle transitions, and unhealthy dietary patterns have been identified as the primary drivers of the increasing disease burden. This study provides a systematic analysis of the epidemiological characteristics of T2DM among individuals aged 40 years and older, focusing on demographic and regional disparities as well as the key biological and behavioral factors contributing to disease development.
Keywords: Type 2 diabetes mellitus; epidemiology; metabolic syndrome; prevention; glycemic control.